2007
DOI: 10.1111/j.1365-2028.2006.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Are fisheries management, measures in Lake Victoria successful? The case of Nile perch and Nile tilapia fishery

Abstract: Population characteristics from samples collected during bottom trawl surveys of 1998-2000 and 2004-2005 were compared to evaluate the success of the management strategies put in place for Nile perch, Lates niloticus and Nile tilapia, Oreochromis niloticus fisheries in Lake Victoria. Data were analysed using FAO-ICLARM stock assessment tool. Length at 50% maturity (Lm 50 ), asymptotic length (L ¥ ) and maximum age (t max ) attained have decreased whereas fishing mortality (F) and growth curvature (K) have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…The generalist filter feeding Nile tilapia is a very important economic fish in Lake Victoria (OgutuOhwayo, 1990;Njiru et al, 2007) and Lake Mburo (Bwanika et al, 2004;Nagayi-Yawe et al, 2006). Nile tilapia, consumes large amounts of the cyanobacteria Microcystis and Anabaena in its diet (Balirwa, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The generalist filter feeding Nile tilapia is a very important economic fish in Lake Victoria (OgutuOhwayo, 1990;Njiru et al, 2007) and Lake Mburo (Bwanika et al, 2004;Nagayi-Yawe et al, 2006). Nile tilapia, consumes large amounts of the cyanobacteria Microcystis and Anabaena in its diet (Balirwa, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, even with this decline in catches, Lake Victoria still supports a valuable fishery (Abila, 2000;Yongo, Keizire & Mbilinyi, 2005). Currently L. niloticus, R. argentea and O. niloticus constitute the most important commercial fishery in Lake Victoria with a total annual catch estimated at 500,000 t with an export valued at US$250 million (Yongo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Experience of other geographical regions has shown that because of stock depletion, fishers have to put in greater efforts, including the use of smaller mesh sized nets/baskets and increase in fishing hours, to meet the demand. Such increased efforts will lead to larger cropping of juvenile prawn and will inadvertently accelerate stock depletion and impair recruitment (Njiru et al 2006). The likelihood that the number of fishers and fishing hours will increase tremendously in the foreseeable future is eminent and should be prevented.…”
Section: Discussionmentioning
confidence: 96%